The ATPase Domain but Not the Acidic Region of Cockayne Syndrome Group B Gene Product Is Essential for DNA Repair - Brosh, Robert M. (The American Society for Cell Biology, 1999)
Cockayne syndrome (CS) is a human genetic disorder characterized by UV sensitivity, developmental abnormalities, and premature aging. Two of the genes involved, CSA and CSB, are required for transcription-coupled repair (TCR), a subpathway of nucleotide excision repair that removes certain lesions rapidly and efficiently from the transcribed strand of active genes. CS proteins have also been implicated in the recovery of transcription after certain types of DNA damage such as those lesions induced by UV light. In this study, site-directed mutations have been introduced to the human CSB gene to investigate the functional significance of the conserved ATPase domain and of a highly acidic region of the protein. The CSB mutant alleles were tested for genetic complementation of UV-sensitive phenotypes in the human CS-B homologue of hamster UV61. In addition, the CSB mutant alleles were tested for their ability to complement the sensitivity of UV61 cells to the carcinogen 4-nitroquinoline-1-oxide (4-NQO), which introduces bulky DNA adducts repaired by global genome repair. Point mutation of a highly conserved glutamic acid residue in ATPase motif II abolished the ability of CSB protein to complement the UV-sensitive phenotypes of survival, RNA synthesis recovery, and gene-specific repair. These data indicate that the integrity of the ATPase domain is critical for CSB function in vivo. Likewise, the CSB ATPase point mutant failed to confer cellular resistance to 4-NQO, suggesting that ATP hydrolysis is required for CSB function in a TCR-independent pathway. On the contrary, a large deletion of the acidic region of CSB protein did not impair the genetic function in the processing of either UV- or 4-NQO-induced DNA damage. Thus the acidic region of CSB is likely to be dispensable for DNA repair, whereas the ATPase domain is essential for CSB function in both TCR-dependent and -independent pathways.